If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2u+7(u-6)=-2
We move all terms to the left:
-2u+7(u-6)-(-2)=0
We add all the numbers together, and all the variables
-2u+7(u-6)+2=0
We multiply parentheses
-2u+7u-42+2=0
We add all the numbers together, and all the variables
5u-40=0
We move all terms containing u to the left, all other terms to the right
5u=40
u=40/5
u=8
| 6(w+7)-2w=22 | | 1/3x+1/2x=16-6 | | 3(s-3)=5(25+1) | | r/7+39=48 | | -11+4x=6x-5 | | 5x/3-x=7-3 | | 5x/3+x=7-3 | | 3r=2r+18 | | 15=7+2k | | 3x7x=-1 | | 2k÷3=6 | | 8x+1=5x+13 | | 3/5x-8=-15 | | M-(m-1/2)=(m-2/3) | | 25y=5(5)+100 | | 6x=2(x-2)+9 | | x+7=2x+87 | | 1.2(x+4)=12 | | 1/50=x/40 | | 10f-8f=2f | | x/3=15/30 | | 12h=12h= | | 10x-12=6x=x | | g-24=24g= | | 36=f+24f= | | 4-14x=80 | | 5x/3+3=7 | | d/12=6d= | | −7a−28=−7(a+4) | | 3/x=11/33 | | b-12=15b= | | 48/a=4a= |